Regorafenib in older adults with metastatic colorectal cancer: A multi-center, single arm phase II trial - Zittel, Jason; Baran, Andrea M.; Dotan, Efrat; Hubbard, Joleen M.; Noel, Marcus Smith; Hezel, Aram F; Tejani, Mohamedtaki Abdulaziz; Mohile, Supriya Gupta (Journal of clinical oncology, 2023)
12047Background: Metastatic colorectal cancer (mCRC) is a leading cause of death, particularly in older adults. Regorafenib (REGO) is an FDA-approved oral multi-kinase inhibitor for refractory mCRC based on the CORRECT trial results, but older adults were underrepresented with a median age of 61 (54-67). This study aimed to evaluate REGO safety in older adults with mCRC and assess the feasibility of using geriatric assessment (GA) to predict toxicity risk. Methods: 27 subjects (PTs) enrolled (median age 73, range 65-85) and started at 120mg of REGO for 21 days of a 28-day cycle with provider discretion to escalate to full dose of 160mg after cycle 1. GA was conducted at enrollment, 4 weeks later, and then every 3 months to monitor for any deterioration. GA assessed 8 geriatric domains (comorbidity, functional status, physical performance, cognition, psychological state, nutrition, medication review, and social support) using validated tools. Primary objective was to assess grade 3-5 toxicity rate, with secondary objectives evaluating REGO efficacy and exploring baseline GA and toxicity risk associations. Kaplan-Meier method was used to estimate median overall survival (OS) and progression-free survival (PFS) from date of consent. Continuous GA measures were compared using non-parametric Wilcoxon rank-sum test, and binary GA measures were compared using Fisher's exact test. Results: Of 27 PTs enrolled, 15 were male, 12 were female, and 19 identified as white. At baseline, 77.7% of PTs had at least 3 (1-9) GA impairments. Physical performance (80.8%), comorbidity (75%), and cognition (69.2%) were the most prevalent impaired GA domains. 40% required dose reduction by end of cycle 2, and none escalated to full dose. 55% of PTs completed cycle 3. Main reasons for drug discontinuation were disease progression (80%) and toxicity (12%). 74.1% of PTs experienced at least one treatment-related grade 3-4 toxicity. Fatigue (33%), hypertension (30%), and hand-foot syndrome (15%) were the leading grade 3-4 toxicities. Median OS was 5.6 months (95% CI: 3.6-12.2m), and median PFS was 2.8 months (95% CI: 2.5-3.4m). There was no significant difference in baseline GA measures between those who experienced toxicities and those who did not. No statistically significant toxicity risk was associated with any baseline GA impairment. The prevalence of impaired mini-nutritional assessment increased over 4 weeks (58% to 91%, p < 0.01), and median Short Physical Performance Battery (SPPB) scores decreased (7 to 6, p = 0.03). Conclusions: The study found that older adults with mCRC had comparable survival with REGO but experienced high toxicity. This may be ameliorated by recently published step-wise REDOS dosing method and should be considered in older adults with mCRC. The study confirms the feasibility of implementing GA within clinical trials. More data is needed on the role of GA in predicting toxicity with targeted therapies. Clinical trial information: NCT02466009.